2009
DOI: 10.1016/j.exer.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the meibomian gland

Abstract: The purpose of this study was to characterize the age-related changes of the mouse meibomian gland. Eyelids from adult C57Bl/6 mice at 2, 6, 12 and 24 months of age were stained with specific antibodies against peroxisome proliferator activated receptor gamma (PPARγ) to identify differentiating meibocytes, Oil Red O(ORO) to identify lipid, Ki67 nuclear antigen to identify cycling cells, B-lymphocyte-induced maturation protein-1 (Blimp1) to identify potential stem cells and CD45 to identify immune cells. Meibom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 35 publications
10
99
0
2
Order By: Relevance
“…These renderings show that MG from a young mouse contains multiple, large acini with a high lipid volume, whereas MG from an old mouse have fewer acini with markedly reduced lipid volume. These findings are consistent with earlier results showing reduced gland size in older mice (Nien et al, 2009) and further indicate that aging mouse MG show acinar "dropout" similar to that detected in humans. Overall, this study demonstrates that NLO array tomography may be a useful approach to studying the 3-D structure of tissues and glands and that it provides quantitative, volumetric measurements with femtolitre resolution.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…These renderings show that MG from a young mouse contains multiple, large acini with a high lipid volume, whereas MG from an old mouse have fewer acini with markedly reduced lipid volume. These findings are consistent with earlier results showing reduced gland size in older mice (Nien et al, 2009) and further indicate that aging mouse MG show acinar "dropout" similar to that detected in humans. Overall, this study demonstrates that NLO array tomography may be a useful approach to studying the 3-D structure of tissues and glands and that it provides quantitative, volumetric measurements with femtolitre resolution.…”
Section: Introductionsupporting
confidence: 93%
“…Recently, we have shown that the MG of mice develop age-related changes similar to those observed in humans, including reduced gland size and decreased proliferative potential (Nien et al, 2009). Since previous studies of human MGD using transillumination biomicroscopy (meibography) have identified "gland dropout" as a pathognomonic feature, (Jester et al, 1982) the purpose of this study was to develop an imaging approach to generate quantifiable volumetric reconstructions of the mouse MG that could assess gland "dropout" and measure the total, cellular, and lipid volume.…”
Section: Introductionmentioning
confidence: 78%
“…Modifications on MG structure have been identified with age as, an altered localization of the peroxisome proliferator-activated receptor-ɣ (PPAR-ɣ), a lipid-activated hormone receptor that regulates lipid synthesis and cell differentiation [16,17] or MG atrophy [18]. In research on mouse model, some authors have found changes in the mucocutaneous junction and glandular atrophy through a loss of meibocyte progenitors [18].…”
Section: Aging and Lacrimal Discomfortmentioning
confidence: 99%
“…1,2 This altered lipid production could subsequently result in increased tear evaporation, increased tear osmolality, and dryness symptoms. 3,4 There is currently little information available to prove a direct link between meibomian gland atrophy and CL discomfort.…”
mentioning
confidence: 99%